Food reinforcement function after deprivation on eating behavior in rats: a link between motivation and conditions - Díaz-Reséndiz, Felipe de Jesús (Universidad Autónoma de Tamaulipas, 2013)
Food intake can be altered, without changing food properties, through modification of the inter access-to-food intervals and access-to-food duration. Understanding the influence of each of these variables on food intake will allow a better comprehension of problems of public health, such as obesity, and understanding of excessiveness or deficiency in the consumption of food. In this study both variables were manipulated to observe their effects on food intake behavior in rats. A factorial design was used to combine three different inter access-to-food intervals (720, 18 and 45 minutes), with three levels of access-to-food duration (40, 10 and 2.5 minutes). Food intake was compared with a base line consumption of 15 days of free access-to-food. It was found that increasing the intervals of access-to-food yielded more food intake. Decreasing the time of access-to-food controlled faster reactions to the opportunity to eat than when food was available at the time. This decrease also controlled that every opportunity to consume food was taken. When duration of access-to-food was increased, body weight increased too. Results from this basic research study contribute to knowledge about the possible iatrogenic effects of inadequate exposure to periods of restriction and access to food, characteristic of obesity and eating disorders. From a theoretical standpoint, this study is a step forward in the conceptual integration of two separated areas of knowledge in experimental analysis of behavior.